Managing Inclusive Educational Infrastructure for Children with Autism Spectrum Disorder: A Case Study of Adaptive and Child-Centered Facility Governance - Syarifudin, Fahmi; Komariah , Aan; Kurniady, Dedy Achmad; Ramadhan, Rifky Aditya (International Journal of Educational Management and Innovation, 2026)
Background. This study addresses the need for effective management of inclusive educational infrastructure for children with Autism Spectrum Disorder (ASD). While inclusive education research has largely focused on pedagogy and instructional practices, there has been limited attention paid to infrastructure management as a central component of inclusive educational governance, particularly in early childhood settings. Appropriate infrastructure is essential for supporting both learning and therapeutic processes for children with ASD. Method. This research employed a qualitative case study design at the EDUfa Autism Therapy Center. Data were collected through systematic observations, in-depth interviews with therapists, parents, and administrative staff, and document analysis. This approach enabled a contextual understanding of how inclusive infrastructure is planned, utilized, and managed within an integrated educational therapeutic environment. Result. The findings show that EDUfa’s infrastructure, such as calming therapy rooms, flexible learning spaces, sensory transition zones, and educational toilets, is intentionally designed to accommodate the sensory, cognitive, and emotional needs of children with ASD. Infrastructure management practices are characterized by responsiveness, adaptability, and collaborative stakeholder involvement in planning and evaluation. Simple innovations, such as daily facility condition reports and low-tech monitoring systems, support the sustainability and functionality of facilities. Conclusion. The study concludes that inclusive educational infrastructure management extends beyond technical operations to reflect inclusive educational values. Theoretically, it contributes to inclusive educational management by positioning infrastructure as an active managerial element in inclusive early childhood education. Practically, the EDUfa model offers replicable strategies for creating responsive, child-centered learning environments.